1969
DOI: 10.1111/j.1469-185x.1969.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Biological Controls on Bivalve Shell Mineralogy

Abstract: Summary Bivalves lay down two forms of calcium carbonate in their shells, aragonite and calcite. Shells may be wholly aragonitic, or may contain both aragonite and calcite, in separate monomineralic layers. Shells are built up of several layers of distinct aggregations of calcium carbonate crystals. These aggregations are referred to as shell structures and their general features are described. Aragonite occurs as prismatic, nacreous, crossed‐lamellar, complex crossed‐lamellar and homogeneous structures. Calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 44 publications
5
69
0
2
Order By: Relevance
“…Only those metals exhibiting significant patterns or anomalies will be discussed herein. Bivalve shells from time to time may contain small inclusions of foreign matter (Kennedy et al 1969), so peaks that were primarily driven by 1 or 2 data points are not considered to be significant. The results of parallel scans run on the same shell (Fig.…”
Section: Trace Element Scansmentioning
confidence: 99%
“…Only those metals exhibiting significant patterns or anomalies will be discussed herein. Bivalve shells from time to time may contain small inclusions of foreign matter (Kennedy et al 1969), so peaks that were primarily driven by 1 or 2 data points are not considered to be significant. The results of parallel scans run on the same shell (Fig.…”
Section: Trace Element Scansmentioning
confidence: 99%
“…Some groups precipitate predominantly aragonite, such as scleractinian corals (1) and calcareous chlorophytes (2), others mostly calcite, such as foraminifera (3), coccolithophores (4), and corraline Rhodophytes (2), and some a chimera of the two (5,6). The geological prevalence of the different groups is thought to be caused by successions in sea water chemistry: periods with relatively high Ca 2ϩ concentrations and low Mg 2ϩ concentrations (i.e., with low Mg/Ca ratios) have favored organisms precipitating calcite, while periods with relatively high Mg/Ca ratios (e.g., during the Neogene) have favored those forming aragonite (7)(8)(9).…”
mentioning
confidence: 99%
“…Another unusual and unexpected mineral phase, SiCa 2 , was registered only in Zospeum isselianum shells. It is well established that mineralogy and composition of the calcified structure reflect endogenous and exogenous condition in the environment (Dodd, 1967;Kennedy et al, 1969;Carriker et al, 1991). Fritz et al, (1990) indicated that minerals of elemental composition similar to calcium carbonates could be mineralized by mollusks.…”
Section: Freshwater and Subterranean Snailsmentioning
confidence: 99%